Uso de medicamentos inibidores de tirosina quinase por portadores de leucemia mieloide crônica na Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas (HEMOAM) - Menezes, Andreia Duarte (2017)
Chronic myeloid leukemia (CML) is a clonal myeloproliferative disease characterized cytogenetically by the presence of the Philadelfia chromosome, resulting from the reciprocal translocation between the BCR and ABL genes; Produces an abnormal protein with excessive tyrosine kinase activity responsible for increased cell proliferation, altered cell adhesion and inhibition of apoptosis. The inhibitors of tyrosine kinase represent an advance in the treatment of CML, because when acting as selective competitors and blockers of the cells bearing the BCR-ABL rearrangement, they lead to the possible hematological and cytogenetic remission. However, the use of these drugs requires the knowledge of several aspects related to the treatment, both by the health team and patients. It is fact the incorret use of medications can reduce their effectiveness, increase their toxicity and influence adherence. The present observational and transversal study had as objective to evaluate the conditions of use of tyrosine kinase inhibitors (ITQs) by CML carriers attended in HEMOAM and to evaluate the adherence to the drug therapy. Among 133 patients with CML , 63 were interviewed in the period from December 2015 to April 2016, with a mean age of 51.5 years, of which 60% were men and 52.4%, with an income of between 2 and 3 minimum wages. Regarding knowledge about aspects related to the use of ITQ, 95.2% were taking it at the right time, 93.7% did not use other medications concomitantly, 63.5% kept it in a suitable place. Approximately 97% of patients received prior guidance from the physician on the use. The Morisky and Green test was used to estimate adherence to treatment and a 46% compliance was found. The results showed that patients had a good understanding of their disease and drug therapy, as well as adherence to the use of ITQs was regular and similar to that of other studies